The family as a contested arena : voices of discontent in Charles Mungoshi's works in Shona and English. - Ndlovu, Thabisani (My University, 2011)
This thesis explores ideologies of intimate attachments and offers an overall critique of the ideology(ies) of family as evinced by Mungoshi’s ironic treatment of this theme. A close reading of Zimbabwe through the oft-cherished institution of family, an argument is made here, multiplies fields and possibilities of meaning beyond the struggle against colonialism and cultural imperialism. It is suggested that instead of viewing the family as political allegory and unitary, it is profitable to perceive it as consisting of a multiplicity of contesting voices and/or interests. These voices include those of children, women, young adults, lone parents, homosexuals and heterosexual men with thwarted gender identities. Through familial contestation and conflict, Mungoshi offers for critique various matrices of power located within the family and affords us an opportunity to read a country and its literature from the “everydayness” of characters’ lived experience especially the confusions, anxieties and ambiguities. Thus, much as the thesis is cognizant of wider socio-political contexts in the work of Charles Mungoshi, more attention is given to conflict or contestation within the institution of the family in which, as Mungoshi suggests, there is a fluid configuration of power and authority. Conflict and contestation express a desire to reformulate familial and, by extension, social relationships. Similarly, Mungoshi suggests that gendered identities are subject to various claims, negotiations, resistance and refutations. This thesis is the one attempt that discusses Mungoshi’s work in one volume, across the two languages and three genres he writes in to generate a more subtle, more layered reading by examining the family trope. In other words, there has been no systematic and lengthy discussion of the family and its related concepts of home, belonging, childhood, parenthood, gender and sexualities – all of which Mungoshi explores to address particular familial and societal concerns. This thesis then is an attempt to systematically evaluate Mungoshi’s representation of family and issues attendant to this subject by paying particular attention to voices of discontent.